If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 29 + -3x = 23(2x + -3) Reorder the terms: 29 + -3x = 23(-3 + 2x) 29 + -3x = (-3 * 23 + 2x * 23) 29 + -3x = (-69 + 46x) Solving 29 + -3x = -69 + 46x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-46x' to each side of the equation. 29 + -3x + -46x = -69 + 46x + -46x Combine like terms: -3x + -46x = -49x 29 + -49x = -69 + 46x + -46x Combine like terms: 46x + -46x = 0 29 + -49x = -69 + 0 29 + -49x = -69 Add '-29' to each side of the equation. 29 + -29 + -49x = -69 + -29 Combine like terms: 29 + -29 = 0 0 + -49x = -69 + -29 -49x = -69 + -29 Combine like terms: -69 + -29 = -98 -49x = -98 Divide each side by '-49'. x = 2 Simplifying x = 2
| 4a-9(3-a)= | | 4(-2a+6)+a= | | -5(-7-3x)-7= | | 2(x+6)-9x= | | 8+5(3x-4)=7(x-12) | | -8(2n-4)+5= | | -7n+4(-6+3n)= | | 10d+5d=2 | | 4x^2-40x+103=0 | | -3-8(-5a-1)= | | 2x-5(x+2)=-8-2x | | .50t+.33t=10 | | -3-8(-5-1)= | | 2-c=-6c+-3 | | 9a-4(2a+5)= | | -(x+1)=2(5-x) | | -12=2+7v | | 49.8-6-18.8= | | 2*cos(4x)=0 | | x^2-2x-15624=0 | | 9a-4(-5a-1)= | | 0.3y^2+0.7y^2-0.2y^2= | | 72=90-x | | 8-3(6-6x)= | | .4x-.9y=.7 | | 9=2(4-x)+7 | | 3x(4x+3)= | | 13x-7=42+6x | | 12r+36=2r+10-3r | | (x-9)(x-9)=0 | | (8a+6)2=34 | | 13-8y=5y+2 |